High‐fat diet‐induced metabolic disorders impairs 5‐HT function and anxiety‐like behavior in mice. (9th December 2015) - Zemdegs, Juliane; Quesseveur, Gaël; Jarriault, David; Pénicaud, Luc; Fioramonti, Xavier; Guiard, Bruno P.
Abstract : Background and Purpose: The link between type 2 diabetes mellitus (T2DM) and depression is bidirectional. However, the possibility that metabolic disorders may elicit anxiogenic‐like/depressive‐like symptoms or alter the efficacy of antidepressant drugs remains poorly documented. This study explored the influence of T2DM on emotionality and proposed a therapeutic strategy that might be used in depressed diabetic patients. Experimental Approach: Mice were fed a high‐fat diet (HFD) and subjected to a full comprehensive metabolic and behavioural analysis to establish correlations between metabolic and psychiatric disorders. In vivo intra‐hippocampal microdialysis was also applied to propose a mechanism underpinning the phenotype of mice fed the HFD. Finally, we tested whether chronic administration of the selective 5‐HT reuptake inhibitor escitalopram or HFD withdrawal could reverse HFD‐induced metabolic and behavioural anomalies. Key Results: The increased body weight, hyperglycaemia and impaired glucose tolerance in response to HFD were correlated with anxiogenic‐like/depressive‐like symptoms. Moreover, this phenotype was associated with decreased extracellular 5‐HT levels in the hippocampus which may result from increased sensitivity of the dorsal raphe 5‐HT1A autoreceptor. Interestingly, the beneficial effect of prolonged administration of escitalopram was abolished in HFD‐fed mice. On the contrary, HFD withdrawal completely reversed metabolic impairments and positively changed symptoms of anxiety, although some behavioural anomalies persisted. Conclusions and Implications: Our data provide clear‐cut evidence that both pathologies are finely correlated and associated with impaired 5‐HT mediated neurotransmission in the hippocampus. Further experiments are warranted to define the most adequate strategy for the treatment of such co‐morbidity. Linked Articles: This article is part of a themed section on Updating Neuropathology and Neuropharmacology of Monoaminergic Systems. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v173.13/issuetoc